Cyclic stretch decreases TRPC4 protein and capacitative calcium entry in rat vascular smooth muscle cells - Lindsey, S.H.; Tribe, R.M.; Songu-Mize, E. (Life sciences (1973), 2008)
We investigated whether cyclic stretch affects TRPC4 or TRPC6 expression and calcium mobilization in cultured vascular smooth muscle cells. In aortic and mesenteric smooth muscle cells isolated from male Sprague–Dawley rats, TRPC4 expression was decreased after 5 h stretch and remained suppressed through 24 h stretch. After removal of the stretch stimulus, TRPC4 expression recovered within 2 h. Stretch did not affect TRPC6 expression. Stretch also decreased capacitative calcium entry, while agonist-induced calcium influx was increased. Similar results were obtained in primary aortic smooth muscle cells. TRPC4 mRNA levels were not decreased in response to mechanical strain. TRPC4 downregulation was also achieved by increasing extracellular calcium and was attenuated by gadolinium and MG132, suggesting that TRPC4 protein is regulated by intracellular calcium concentration and/or the ubiquitin-proteasome pathway. These data suggest that stretch-induced downregulation of TRPC4 protein expression and capacitative calcium entry may be a protective mechanism to offset stretch-induced increases in intracellular calcium.